Writing the Indian Ocean in selected fiction by Joseph Conrad, Amitav Ghosh, Abdulrazak Gurnah and Lindsey Collen - Lavery, C (2014)
Tracked and inscribed across the centuries by traders, pilgrims and imperial competitors, the Indian Ocean is written into literature in English by Joseph Conrad, and later by selected novelists from the region. As this thesis suggests, the Indian Ocean is imagined as a space of littoral interconnections, nomadic cosmopolitanisms, ancient networks of trade and contemporary networks of cooperation and crime. This thesis considers selected fiction written in English from or about the Indian Ocean—from the particular culture around its shores, and about the interconnections among its port cities. It focuses on Conrad, alongside Amitav Ghosh, Abdulrazak Gurnah and Lindsey Collen, whose work in many ways captures the geographical scope of the Indian Ocean: India, East Africa and a mid-point, Mauritius. Conrad’s work is examined as a foundational text for writing of the space, while the later writers, in turn, proleptically suggest a rereading of Conrad’s oeuvre through an oceanic lens. Alongside their diverse interests and emphases, the authors considered in this thesis write the Indian Ocean as a space in and through which to represent and interrogate historical gaps, the ethics and aesthetics of heterogeneity, and alternative geographies. The Indian Ocean allows the authors to write with empire at a distance, to subvert Eurocentric narratives and to explore the space as paradigmatic of widely connected human relations. In turn, they provide a longer imaginative history and an alternative cognitive map to imposed imperial and national boundaries. The fiction in this way brings the Indian Ocean into being, not only its borders and networks, but also its vivid, sensuous, storied world. The authors considered invoke and evoke the Indian Ocean as a representational space—producing imaginative depth that feeds into and shapes wider cultural, including historical, figurations.